2022
DOI: 10.1111/ejss.13274
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of rainfall types and antecedent soil moisture on runoff generation at a hillslope of red soil region

Abstract: The runoff threshold is one of the important parameters in hillslope hydrology. Information on the combined roles of rainfall types and antecedent soil moisture in the runoff generation threshold is still scarce. Therefore, we linked the runoff generation behaviours of a 150‐m hillslope with rainfall types and antecedent soil moisture conditions during a 4‐year observation period between January 2017 and December 2020 in the red soil region of China. We found that the surface runoff of a hillslope could be mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Rainfall intensity severely affects flow-discharge lag time, and high-intensity and long-duration rainfall shortens the response time of river runoff [51]. Ordinary rainfall, on the other hand, requires the soil to reach the moist threshold for runoff to occur [14]. Rainfall and rainfall intensity are also important factors in the lag time of riverine flow discharge [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rainfall intensity severely affects flow-discharge lag time, and high-intensity and long-duration rainfall shortens the response time of river runoff [51]. Ordinary rainfall, on the other hand, requires the soil to reach the moist threshold for runoff to occur [14]. Rainfall and rainfall intensity are also important factors in the lag time of riverine flow discharge [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Antecedent rainfall increases soil moisture and reduces soil infiltration, so the significance of antecedent rainfall in sediment-load processes cannot be understated. Studies have confirmed that the runoff coefficient can double when the soil is moistened by antecedent rainfall, due to the acceleration of runoff generation with moist soils [14,15]. Antecedent rainfall increases soil moisture, improves runoff conversion efficiency, accelerates riverine runoff discharge [13,16], enhances water erosion, and increases riverine sediment loads.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that the crusted soil pores had a feature of a large number of nearly circular small pores, with the pore number and circularity decreased, while the equivalent diameter increased with the slope, mainly due to differences in the run‐off and sediment process, and crust formation process on slopes with different gradients. Based on a 4‐year field experimental study, Wang, Gao, et al (2022) demonstrated that rainfall strength and antecedent soil moisture conspire to determine the threshold of runoff generation, a key for runoff characterization. Hourly maximum rainfall intensity was the main contributor to runoff generation for the relatively slight rainfall events, while the rainfall amount determined the rainfall type with larger amounts and intensities.…”
Section: Figurementioning
confidence: 99%
“…Fubiao [23] studied erosive rainfall and sediment yield traits in the Puxiang River Basin in western Yunnan Province, unveiling distinct impacts of rainfall factors on runoff depth and sediment yield across varied land use types. Wanghe [24] investigated sediment production regularities on exposed slopes in red soil regions under diverse rainfall types, revealing a linearly positive correlation between runoff depth, soil erosion, and rainfall metrics such as precipitation (P), maximum 30 min rainfall intensity (I 30 ), and rainfall kinetic energy (E). Zhao Y [25] conducted various lab experiments examining rainfall effects on runoff and soil erosion, noting significant differences in the hydrograph, sediment graph, soil water content, and infiltration depth.…”
Section: Introductionmentioning
confidence: 99%